Hybrid improvement and reconstruction based on prognostic breeding selection criteria - Ipsilandis, Constantinos G.; Greveniotis, Vasileios; Pampouktsi, Panagiota; Sioki, Evangelia; Tsapikounis, Fanis A. (Emirates Journal of Food and Agriculture, 2019)
In order to faster and more efficiently select maize inbred lines as parents for maize hybrids, a multi-year evaluation was conducted under both honeycomb methodology schemes and classic randomized complete block designs. Combined yield and stability calculations were used. The initial genetic material was developed from F2 of a commercial F1 maize hybrid.1200 F2 plants were used at an intra-row distance of 1.25m and the inter-row distance was 1.08m in a NR-0 honeycomb design. Combined Half-sib and S1 evaluation was performed for oriented crosses. After successive selfing generations S1 to S7 progenies were developed. Three types of crosses were performed a) Formation of HS families, b) Diallel crosses between S4 and also S5 recombinant lines, and c) Crosses of these lines to the freely available inbred line B73. Crosses between high yielding S-lines to common foreign parent led to limited heterotic phenomena and relative low yielding performance. Heterobeltiosis was found near zero or negative, proving that such kind of parents cannot contribute in high yielding crosses because of the accumulation of useful additive alleles in the improved parent, and additive alleles are not favoured in heterozygote condition. Crosses between improved lines were generally high, but they based their productivity mainly on additive gene action. Prognostic breeding is more accurate when selection is applied for exploitation of additive gene action. CV was a good stability criterion, but CC proved confusing for selecting crosses. Productivity index P exhibited the superiority of the best lines that showed high and stable performance across years. The procedure resulted in high yielding inbred lines bypassing population improvement and thus shortened the whole evaluation process.